醫案을 통한 신종 인플루엔자의 한의학적 대처방안 - 안상영(Ahn Sang-young); 한창현(Han Chang-hyun); 권오민(Kwon Oh-min); 박상영(Park Sang-young); 안상우(Ahn Sang-woo) (대한한의학원전학회지, 2009)
Background: The recent outbreak of the novel strain of influenza A (H1N1) virus has raised a global concern of the future risk of pandemic. Traditional Korean Medicine(TKM) has been combatting against contagious diseases and developed its own particular and efficient way in treating those diseases. Objectives: Provide a distinctive and effective TKM method in understanding the principles of treatment, prevention, and contraindications against influenza A through case histories. Method: We revised case histories of eminent doctors of Ming and Qing dynasties according to their clinical manifestations similar to those of influenza A. We also verified prescriptions of the 『Dong-uibogam(東醫寶鑑)』 through examining clinical practices of China today. Results: 1. The subtypes of Warm disease; Wind Warmth and Pestilence has the most similar clinical manifestation in comparison to Influenza A. Specifying these terms is important in recognizing and classifying various diseases under the name of Warm disease. 2. TKM considered not only external factors but also individual factors like general condition, diet, emotion, constitutional types, etc in the treatment of febrile diseases. 3. TKM developed a new way in the treatment of contagious diseases. considering the characteristics of each pathogen. TKM described the Warm pathogen being light as a feather, which enters through the nose, principally affecting the Lung. Therefore, they emphasized treatment with Pungent Sweet Cooling Moistening[辛甘凉潤] method. 4. As the conservation of fluid and humor is the primordial concern in the treatment of Warm disease, they restricted release of the exterior with pungent-warm and purgation method. The purgation methods was used exclusively to decrease fever and preserve fluid and humor. 5. The only differentiating characteristics of Influenza A with seasonal influenza are vomiting and diarrhea. Case research revealed the possibility of these manifestations to be a mechanism of restoration. 6. TKM provides alimento prevention method like Mint Pear Porridge, mung bean, and etc also combination of herbal medicine. Also emphasized in the conservation of essence for the prevention of contagious diseases. Conclusions: TKM developed its unique way in understanding the pathogenesis, diagnosis, treatment, and prevention of contagious diseases and formed its independent scheme of Warm Disease. This knowledge in febrile contagious disease is relevant today in providing diverse treatment and prevention for influenza A. KCI Citation Count: 2